Two new species of Tricorythus Eaton 1868 (Ephemeroptera, Tricorythidae) from Zambia - Kluge, Nikita J. (Zootaxa, 2016)
Larvae, subimagoes, imagoes of both sexes and eggs of Tricorythus furcifer sp.n. and T. tener sp.n. are described based on reared material from Zambia. Larvae of both species closely resemble larvae of T. varicauda (Pictet 1843), while genitals of male imagoes are different, being especially unusual in T. furcifer. A new locality for Tricorythus tinctus Kimmins 1956 is recorded in Zambia.